Social Bonding Experiences Facilitating Desistance in Adolescence - Abeling-Judge, David (Crime & delinquency, 2021)
Desistance from crime involves nuanced consideration of external and internal theories of change and methodological challenges to accurately capture positive change. Although desistance is expected for adult offenders, the onset of change in adolescence has not received sufficient attention. The current study explores the potential impact of specific social bonding experiences, to school, parents, and peers, on desistance among juvenile offenders using the Pathways to Desistance study. Findings indicate that school socialization can facilitate positive change, as can maternal bonding and changes in peer networks. The study also creates opportunity to revisit how theoretical perspectives may be guided by age specific patterns of offending.